1982
DOI: 10.1002/1097-0142(19820901)50:5<821::aid-cncr2820500502>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy (vincristine, adriamycin, cyclophosphamide, and 5-fluorouracil) in the treatment of children with malignant hepatoma

Abstract: Members of Childrens Cancer Study Group and the Pediatric Division of the Southwest Oncology Group conducted a study of chemotherapy for children with malignant liver tumors. All patients received vincristine, cyclophosphamide, Adriamycin and 5‐fluorouracil in 6 weekly cycles for one year. Surgical resection and irradiation were employed when indicated. Between January 1976 and August 1978, 62 patients were entered on study; one was rejected for a protocol error, and ten had inadequate trials of chemotherapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
4

Year Published

1985
1985
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(61 citation statements)
references
References 4 publications
3
54
0
4
Order By: Relevance
“…Efforts using chemotherapy to increase the percentage of children able to undergo resection were not initially encouraging. 5 It wasn't until 1982, when Evans et al 12 reported the results of a cooperative CCSG and Southwest Oncology Group (SWOG) study, that combination chemotherapy was shown to affect a significant percentage (12/27) of unresectable liver malignancies. In that same year, Weinblatt et al 13 reported that 7 of 8 (87%) unresectable childhood hepatic malignancies treated with chemotherapy exhibited a pronounced clinical response; four HEP children were able to have complete surgical excision of residual disease and one HCC patient had complete disappearance of all disease without surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts using chemotherapy to increase the percentage of children able to undergo resection were not initially encouraging. 5 It wasn't until 1982, when Evans et al 12 reported the results of a cooperative CCSG and Southwest Oncology Group (SWOG) study, that combination chemotherapy was shown to affect a significant percentage (12/27) of unresectable liver malignancies. In that same year, Weinblatt et al 13 reported that 7 of 8 (87%) unresectable childhood hepatic malignancies treated with chemotherapy exhibited a pronounced clinical response; four HEP children were able to have complete surgical excision of residual disease and one HCC patient had complete disappearance of all disease without surgery.…”
Section: Discussionmentioning
confidence: 99%
“…HCC staging included: stage I (2), stage II (2), stage III (12), and stage IV (5). Twenty-two patients (14 HCC and 8 HEP) were initially treated elsewhere and subsequently transferred, 20 of whom were felt unresectable by the referring surgeons and 2 who had residual disease following resection.…”
Section: Stagingmentioning
confidence: 99%
“…[5][6][7][8] Instead of lipophilic SMANCS, we used the combination of THP-ADR, CDDP, and 5-FU for the treatment of hepatoblastoma because their antitumor effects have been In addition, ADR and CDDP are drugs with the highest hepatic extraction." A derivative of ADR, THP-ADR has antitumor effects similar to those of ADR and is less cardiot~xic.~ Since THP-ADR, CDDP, and 5-FU are not lipophilic, we made them into a powder and dispersed them in Lipiodol by ultrasonic treatment.…”
Section: Adverse Eflectsmentioning
confidence: 99%
“…Male HB patients are greater in number than female HB patients. The incidence rate of HB in Southeast Asia is higher than those in Europe and North America (Evans et al, 1982). In the 1970s, the main treatment of HB came in the form of a single surgery, with no chemotherapy after operation; at that time, the overall HB survival rate was only 20% to 30% (Evans et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of HB in Southeast Asia is higher than those in Europe and North America (Evans et al, 1982). In the 1970s, the main treatment of HB came in the form of a single surgery, with no chemotherapy after operation; at that time, the overall HB survival rate was only 20% to 30% (Evans et al, 1982). Since the 1980s, surgical therapy combined with chemotherapy, especially platinum chemotherapy, has significantly improved prognosis; and the 5-year survival rate increased by about 75% (Towu et al, 2004;Tiao et al, 2005).…”
Section: Introductionmentioning
confidence: 99%